ARGUMENT ON THE ONTOLOGY REQUIRED BY NATURAL DESIRES: FINDING THE WATER OF LIFE WHERE OTHERS DROWN - Taslaman, Caner (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
Natural desires are among the most fundamental features of mankind. In this article six natural and fundamental desires will be covered: will to live, to be free of fear, to be happy, to have purpose, to acquire knowledge to be free of doubt, and to be treated well by others. The fulfilment of all these natural and fundamental desires requires a God-centred ontology. The best explanation for the reason why these fundamental desires that are independent from each other, all require the same ontology is that they are planted by God. In addition, the desires will be evaluated in their relation to the attributes of God, the Hereafter and religions.